A step forward to develop pharmacist with cosmeceutical knowledge in community pharmacy setting: a pilot study - Ab. Hadi, Hazrina; Azman, Amirah (2018)
Objective: the objective of this study is to evaluate the knowledge of the undergraduate pharmacy student on the cosmetic subject in terms of ingredients, indications and stability to be used by specific customer, as well as to assess the confidence of the students to counsel on cases related to cosmetics in terms of selecting the right function and products to get the best outcome. Methods: A cross-sectional, prospective, pretest-posttest pilot survey was conducted among undergraduate pharmacy students from IIUM that chose cosmetics subject as their elective course. Respondents were asked to answer a set of questionnaire which consist of three parts namely Part A: Demographic, Part B: Knowledge on cosmetic subject, and Part C: Confidence to counsel on cosmetics-related cases. Content validity was assessed, internal consistency was determined, and descriptive and inferential statistics were analysed by using SPSS version 22.0. Results: The internal consistency for Part B and Part C were 0.617 and 0.798 respectively. Overall, 51 participants has been participated in the study with 94.1% of them was female, and 98.0% of them age ranged within 21-23 years old. All of the respondents were second year students from IIUM. The mean +standard deviation (SD) for knowledge before cosmetics subject was taught was 4.80 + 1.811 while after the subject was taught was 7.96 + 0.999. The increment in level of knowledge was significant (p <0.001). Meanwhile, the mean + standard deviation (SD) for confidence to counsel on cosmetics-related cases before cosmetics subject was taught was 47.94 + 8.613 while after the subject was taught was 58.82 + 5.070. The increment in level of confidence to counsel on cosmetics-related cases was significant (p <0.001). Conclusion: The level of knowledge on cosmetics subject and the confidence to counsel on cosmetics-related cases were significantly increased after cosmetics subject has been taught.